Investigation of Ship Hull Girder Strength with Grounding Damage - Alie, Muhammad Zubair Muis; Adiputra, Ristiyanto (UI Scholars Hub, 2018)
The objective of the present study is to investigate ship hull girder strength as a result of grounding damage upon longitudinal bending. A bulk carrier and tanker are analyzed and Smith’s Method is adopted and implemented in the analysis program. An efficient solution procedure is performed by assuming the cross-section remains plane and the vertical bending moment is applied to the cross section. As a fundamental case, the damage is simply created by removing the elements from the cross section. Welding residual stress, initial imperfections, and crack extensions are not considered. The grounding damage is made by two conditions, namely those are placed at the center part of the cross section and those located at an asymmetric position. To determine the ultimate strength, which includes the progressive collapse behavior of ship hull with damage, the simply supported scenario is imposed to the cross section and hogging and sagging conditions are taken into account. The results obtained for intact and damage conditions by the in-house program are compared with one another to observe the collapse behavior in advance.